Nowe partie w systemie partyjnym – specyfika Polski - Marmola, Maciej (Polityka i Społeczeństwo, 2021)
During the quarter-century of democracy in Poland, most of the parliamentary parties had a post-communist or post-Solidarity origin. Only three formations without links to the two sides of the Round Table agreement – League of Polish Families (LPR), Self-Defence (Samoobrona) and Palikot’s Movement (Ruch Palikota, now: Your Move) – have achieved political relevance. The analysis of their road to parliament helps to capture the specificity of the success of genuinely new parties in Poland. The factors that affect high electoral support for the aforementioned three parties were: advantageous configuration in Polish party system, strong leadership and articulation of new issues or neglected demands (exploitation of new community division and filling an ideological niche). The fate of LPR and Samoobrona confirms that the last factor seems to be crucial for the success of genuinely new party.